2012
DOI: 10.1186/1742-2094-9-201
|View full text |Cite
|
Sign up to set email alerts
|

Reduced serum concentrations of 25-hydroxy vitamin D in children with autism: Relation to autoimmunity

Abstract: BackgroundAside from the skeletal health affection, vitamin D deficiency has been implicated as a potential environmental factor triggering for some autoimmune disorders. Vitamin D might play a role in the regulation of the production of auto-antibodies. Immunomodulatory effects of vitamin D may act not only through modulation of T-helper cell function, but also through induction of CD4+CD25high regulatory T-cells. We are the first to investigate the relationship between serum levels of 25-hydroxy vitamin D an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 47 publications
9
111
6
1
Order By: Relevance
“…Our results showed that our autistic patients had statistically significant decrease in serum levels of 25-OH vitamin D than healthy controls, with 30% (12 patients) and 60% (24 children) were vitamin D deficient and insufficient, respectively. This is coincident with the findings of Meguid et al [19] and Mostafa G et al [20] who reported reduced level of 25 OH Vitamin D in patients with autism when compared to healthy children. Our results showed that there was improvement of mean childhood autistic rating scale (CARS) after vitamin D supplementation of 400 units daily for 8 weeks but not to the degree to be significant and the improvement was more in patients with vitamin D deficient autistic children.…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that our autistic patients had statistically significant decrease in serum levels of 25-OH vitamin D than healthy controls, with 30% (12 patients) and 60% (24 children) were vitamin D deficient and insufficient, respectively. This is coincident with the findings of Meguid et al [19] and Mostafa G et al [20] who reported reduced level of 25 OH Vitamin D in patients with autism when compared to healthy children. Our results showed that there was improvement of mean childhood autistic rating scale (CARS) after vitamin D supplementation of 400 units daily for 8 weeks but not to the degree to be significant and the improvement was more in patients with vitamin D deficient autistic children.…”
Section: Discussionsupporting
confidence: 77%
“…Numakawa et al highlighted that autistic children had significantly lower 25-hydroxy vitamin D serum levels than healthy children (P < 0.001) (56). Serum 25-hydroxy vitamin D level had meaningful negative correlation with infantile autism rating scale (P < 0.001) (57). These findings suggest that low prenatal vitamin D may act as a risk factor for ASD.…”
Section: Discussionmentioning
confidence: 98%
“…This hormone presents immunomodulation, neuroprotection and antiepileptic properties (47). Prenatal, postnatal and even and neonatal vitamin D supplementation is imperative for ordinary brain activities (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The noticeable rise in the frequency of autism across the last 20 years is due to an increase in medical cautions to avoid the sun exposure because of its increasing of skin cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The ASD cases have reportedly abnormal bone density thus increased risk for fractures 4 . Young and adult cases of ASD have been found to have an increased odds ratio of fracture around hip, forearm and spine 3,5 . Our case reported trivial fall resulting in a closed short oblique fracture pattern and that suggests subnormal bone strength 6 .…”
Section: Discussionmentioning
confidence: 99%